Bilinguals’ Creativity in Nepali English: Sheeba Shah’s Novel The Other Queen (Scholars' Journal, 2021)
This paper attempted to address the issues related to bilinguals’ creativity in Nepali English and their implications for World Englishes in the Nepali context. I purposively selected Sheeba Shah’s (2018) novel The Other Queen, went through the contents, and examined the language used in the novel to investigate the linguistic and literary creativity. In this paper, I employed a theoretical framework derived from Kachru (1985) to describe how English is nativised in the Nepali context to convey the Nepali socio-cultural, political as well as historical information, and explore how Nepali literature written in English exhibits typical bilingual creativity of the Nepali writer. I found that the bilingual writer adopted different linguistic and literary strategies such as direct lexical transfer, code-switching, hybridisation, metaphors and proverbs, loan translation, and nativised discourse strategies to convey a distinct sense of Nepaliness. Evidences justify that the bilinguals’ creativity contributes to develop new canons in Nepali English literature.